Effect of two luting resin cements on translucency and transparency of ceramic laminate veneer - Betamar, Naeima; Bubteina, Najat; Mohamed, Rafa; Mohamed, Saied (Libyan Journal of Science &Technology, 2022)
Statement of problem: Different types of resin cements may harmfully affect the translucency and transparency of esthetic restorations particularly for thin ceramic laminate veneers. Aim: To assess the effect of using two resin cements as luting agent on the transparency and translucency of laminate veneer prepared from IPS Empress ceramic. Materials and methods: Two dual-cured resin cements systems from different manufacturers were used for this study (MetaCem and Totalcem). Fifteen samples of laminate veneers (LVs) were fabricated from IPS e.Max Empress using a ready-made mould to standardize the form and dimension of prepared samples, then the samples were divided into three groups (n=5). Group (Gp1) was e.Max veneer samples without luting cement (control group), and the other two groups (Gp2 and Gp3) were using two cements (test groups). The resin cement was prepared according to the manufacturers' instructions, and then a layer of luting agent was applied on the fitting surface of the veneer samples and cured by light. The translucency and transparency of all samples were evaluated using a spectrophotometer. Results: e.Max veneers without luting cement (Gp1) showed slightly higher absolute translucency (76.8 ±3.3) than MetaCem samples (Gp2) (74.9±3.8), while veneers cemented with Totalcem (Gp3) displayed the lowest value (70.8±3.9). Statistically, found no significant difference between e.Max veneer (Gp1) and the two luting cements (Gp2 and Gp3) (P 0.066) in the absolute translucency. However, a significant difference between the tested groups in their relative translucency was detected (P .047). T-test showed no significant differences between the luting cements types (Gp2 and Gp3) in their absolute and relative translucency (P 0.134 and P 0.178 respectively). Conclusions: The luting cement slightly affect the translucency of the veneer material, however, both cements found to be acceptable and no significant effect on the translucency and transparency of IPS e.Max Empress LVs.